Princes on the Crossroads - Iron Age in the Požega Valley - Potrebica, Hrvoje (2011)
The Early Iron Age communities of the Požega Valley belong to the Kaptol Group which covers the southernmost part of the Hungarian Plain and the adjoining Alpine area, territory spatially peripheral to the “core” of the Hallstatt cultural complex. The site of Kaptol with its two necropolises and the large fortified settlement with long continuity stands out as the so far largest and most important centre of this area. Rich grave goods in elite burials include luxurious sets of defensive arms that are not just prestigious, but also exotic goods imported from distant areas. The transitional position of the Hallstatt centre in Kaptol, within a communication network connecting highly developed cultural and production centres in the Mediterranean with the Hallstatt world in Central Europe, suggests an immense scientific and cultural potential of this site. An important role in this process was played by the Iron Age cultures of the Balkans and Pannonia, such as the Glasinac or the Donja Dolina Culture, which were closely and directly connected with the centre in Kaptol. We also must not forget that Kaptol lies on the very important ancient route linking the Alpine and the Danubian areas. These exchange networks were obviously operated by local elites, a fact which is illustrated by sets of prestigious items in their graves. However, we can discern between at least two categories of such goods – one that is the product of long-distance exchange schemes (e.g. sets of defence weapons) and one of more locally produced items (e.g. decorated whetstones/sceptres). These categories probably reflect different communication levels. It seems that the general exchange network was superimposed over a whole patchwork of regional exchange networks operated by local elites, too. It also seems that individual Iron Age centres within this network did not merely act as passive distributors of goods, but played the more active role of filtering the contents of this exchange and thus modifying their conceptual meaning. As a consequence of its transitional position, Kaptol is the ultimate point of distribution for many specific types of weapons, pottery, and other objects, but it was probably even more important as a place of cultural transfer between major cultural zones in Early Iron Age Europe. If it operated as an active agent in modifying and filtering the conceptual content of that cultural transfer, it had direct influence on the cultural dynamics of the whole Eastern Hallstatt area, and perhaps even beyond. Paradoxically, cultural innovation would start at the “periphery” in such cases. Perhaps it could mean that there is no periphery in the conceptual, but only in the spatial sense.
Projekt MZOS
ENG